Digital Marketing Effect on Decisions to Use Contractor Services: (Case Study on Facebook Fanspage PT. Maswindo Bumi Mas) - Pasau, Paesa; Ramli, Anwar; Wardhana Haeruddin, Muhammad Ilham (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
The purpose of this study was to determine the effect of digital marketing on the decision to use contractor services (a case study on Facebook fanspage of PT Maswindo Bumi Mas). This type of research is associative with a quantitative approach, at the Digital Marketing office of PT Maswindo Bumi Mas, located on Jl. Topaz Blog B. The research was conducted using a simple linear regression analysis technique. The object of this research is the Facebook Fanspage of PT Maswindo Bumi Mas. The data sources used are primary and secondary data, where the Questionnaire is used as a tool to obtain data on the perceptions of PT Maswindo Bumi Mas clients who have carried out a Memorandum of Understanding (MOU). The data testing technique used as a test tool in this study is the validity test, reliability test, normality test, simple linear regression analysis, t (partial) test, test the coefficient of determination. The sample used in this study were PT Maswindo Bumi Mas clients who had signed an MOU of 100 people. The results of the study as a whole show that Digital Marketing has a significant effect on the decision to use the contractor services of PT Maswindo Bumi Mas.